Ḥikmat-i Khāqāniyya : Shāmil-i yak dawra-yi mukhtaṣar-i mantiq, ṭabīʿiyyāt u ilāhiyyāt - Iṣfahānī, Fāḍil-i Hindī Bahāʾ al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Bahāʾ al-Dīn Iṣfahānī (d. 1137/1725), better known as Fāḍil Hindī, was born into a comfortable home in Isfahan. Being a particularly precocious child, he completed his studies in the traditional and the foreign sciences by the age of thirteen, even carrying the title of mujtahid (someone authorized to issue legal opinions in Shīʿī Islam). He then accompanied his father to the court of the Mughal emperor Awrangzīb (r. 1658-1707), where he remained for several years before returning to Isfahan. At a time at which Isfahan was under the spell of the anti-speculative, literalist Akhbārī school in Shīʿism, Fāḍil Hindī was one of the few to engage in philosophy, so much so that one could call him equally a juristic philosopher or a philosophical jurist. The present work is a very readable, complete course in logic and philosophy that bears witness to his originality as a thinker in each of these domains.